Persistence of Listeria monocytogenes: an integrative narrative review - Poutou-Piñales, Raúl A.; Rincón-Gamboa, Sandra M.; Carrascal-Camacho, Ana K. (Frontiers in Microbiology, 2026)
The persistence of Listeria monocytogenes has become a public health problem in food safety due to its ability to survive in humans, animals, industrial environments, and food matrices through mechanisms of genetic, physiological, and ecological plasticity. The objective of this exploratory review was to map and synthesise scientific information published between 2000 and 2025 on the determinants that sustain this phenomenon, integrating clinical, agricultural and industrial, information from a general perspective. The findings show that a limited set of clonal complexes, including CC1, CC2, CC4, CC6, CC9, CC31, CC87, CC121, and CC321, are recurrently associated with episodes of long-term persistence. At the molecular level, genes such as qacH, bcrABC, cadAC, and mdrL, together with stress survival islands (SSI-1 and SSI-2), provide tolerance to quaternary ammonium compounds, metals, and hostile conditions, and the truncated variants of inlA show adaptive trajectories that favour colonisation in food over invasion in humans. In the host, the resistance to bile and the antimicrobials favours progression to invasive infections; since the agricultural systems, soils, and livestock act as chronic reservoirs and in processing plants, the persistence becomes favoured by biofilms formation, structural and construction deficiencies in drains and some equipment, because of the difficulty in accessing all pieces and parts during cleaning. Overall, this review demonstrates that the persistence of L. monocytogenes results from the convergence of genetic, physiological, and environmental factors, and highlights the need for interdisciplinary and comprehensive control strategies aimed at mitigating its impact on the food chain.